Motivation and barriers for business start-up among graduates: A gender difference - Abubakar S. Garba; Lami Rahama Aliyu (Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan, 2017)
The gender issue in entrepreneurship has been researched from different views and dimensions. Some of the studies have focused on distinguishing between male and female entrepreneurs in terms of their personal skills and socio-demographic characteristics and others have attempted to determine individual intention and behavior toward entrepreneurship. The study analyzes gender difference on the perception of motivational factors and barriers for business startup among graduates. The study is conducted in Kano metropolitan using a cross sectional/survey design. The population of the study composes of graduates who are either unemployed or employed for not more than three years and have obtained a Bachelor degree or Higher National Diploma qualification as the basis for selection. Discriminant analysis (DA) is used to investigate gender difference on the basis of perception about the selected variables on business start-up. Discriminant analysis is useful in creating an equation that will minimize the possibility of misclassifying cases in their respective groups or categories. The result shows highly significant discriminant function (p < .000) and indicates that the proportion of the total variability not explained is about 37.7%. The Box’s M is 14.012 with F = 4.638, which is highly significant at p < 0.003. There is evidence to reject the null hypothesis, which states that the groups do not differ on their perception about motivation and barriers for business start-up. It is recommended for future studies to explore the moderating effect of religiosity and culture on business start-up.